Learning Strategies in English Skills used by Good Language Learners in Millennial Era: A Positive Case Study in Universitas Negeri Makassar - Atmowardoyo, Haryanto; Weda, Sukardi; Sakkir, Geminastiti (Universitas Negeri Makassar, 2021)
This article is another part of the research results conducted with the aim of developing a theory of learning English as a foreign language. The other part has been reported in the article entitled Information Technology Used by Good Language Learners in Millennial Era in Solid State Technology Volume 3 Issue 5. Theory development is carried out by utilizing best practice as a data source. The research question is